Novel ichnology and the taphonomic significance of insect related bioerosion in bone - Parkinson, Alexander Haig (My University, 2022)
Insects have been known to negatively impact the preservation of skeletal remains for over a century. In archaeological literature a large percentage of manuscripts merely note damage by insects without providing any substantive description of the observed modifications. Whilst, in palaeontology the descriptions are more comprehensive, but formal ichnotaxonomic diagnosis has been limited. Research in this thesis is presented in the form of six peer-reviewed papers. Papers one to three utilise the ichnotaxonomic method to establish four new ichno-species, across three major continents (Africa, Asia, and South America). The species include Cubiculum inornatus, Osteocallis infestans, Cubiculum copperi and Munitusichnus pascens. Additionally, this research represents the first comprehensive descriptions of bone surface modifications by insects from the Middle Triassic of South America. In doing so pushing back the origins of unique behaviour (osteophagia) amongst insects by some 90 million years. Descriptions of bone surface modifications presented herein also represent the earliest evidence of this behaviour from the African and Asian continents, during the Early Jurassic and Middle Jurassic retrospectively. Papers three and four present the first comprehensive descriptions of Plio Pleistocene aged bone surface modifications by insects, as well as the first reported case of insect damage on hominin skeletal remains, from The Cradle of Humankind, South Africa. Paper five highlights the application of micro-computed tomographic imaging in differentiating between taphonomic post-mortem bone damage, and peri- or anti- mortem pathologies. The initial hypothesis proposed that bone modifications were related to post-mortem insect damage. However, an in-depth MicroCT analysis in conjunction with a differential diagnosis methodology eliminated insects as the potential causative agent, and identified the second reported instance of Osteomyelitis occurring in a Sauropodomorph dinosaur from the Lower Jurassic deposits of China. The last paper presented in this thesis provides a system of grading bone surface modifications in respect of their usefulness in the identification and differentiation of the associated causal agents. The UID Index could potentially have a broad application across several taphonomic subdisciplines. Bone surface modifications thus represent a significant body of evidence which can contribute to a better understanding of peri-, ante- and post-mortem taphonimic processes, providing ethnological insights into the origins and dispersal patterns of ancient behaviours, identify potential instances of behavioural convergence, and have indirectly identified an elusive role player in the carrion feeding niche, during the Mesozoic.
A thesis submitted in fulfilment of the academic requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Geosciences, University of the Witwatersrand, Johannesburg, 2022